Ablation of intact hypothalamic and/or hindbrain TrkB signaling leads to perturbations in energy balance - Ceren Ozek; Derek J. Zimmer; Bart C. De Jonghe; Robert G. Kalb; Kendra K. Bence (Elsevier, 2015)
Objective: Brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin receptor kinase B (TrkB), play a paramount role in the central regulation of energy balance. Despite the substantial body of genetic evidence implicating BDNF- or TrkB-deficiency in human obesity, the critical brain region(s) contributing to the endogenous role of BDNF/TrkB signaling in metabolic control remain unknown. Methods: We assessed the importance of intact hypothalamic or hindbrain TrkB signaling in central regulation of energy balance by generating Nkx2.1-Ntrk2−/− and Phox2b-Ntrk2+/− mice, respectively, and comparing metabolic parameters (body weight, adiposity, food intake, energy expenditure and glucose homeostasis) under high-fat diet or chow fed conditions. Results: Our data show that when fed a high-fat diet, male and female Nkx2.1-Ntrk2−/− mice have significantly increased body weight and adiposity that is likely driven by reduced locomotor activity and core body temperature. When maintained on a chow diet, female Nkx2.1-Ntrk2−/− mice exhibit an increased body weight and adiposity phenotype more robust than in males, which is accompanied by hyperphagia that precedes the onset of a body weight difference. In addition, under both diet conditions, Nkx2.1-Ntrk2−/− mice show increased blood glucose, serum insulin and leptin levels. Mice with complete hindbrain TrkB-deficiency (Phox2b-Ntrk2−/−) are perinatal lethal, potentially indicating a vital role for TrkB in visceral motor neurons that control cardiovascular, respiratory, and digestive functions during development. Phox2b-Ntrk2+/− heterozygous mice are similar in body weight, adiposity and glucose homeostasis parameters compared to wild type littermate controls when maintained on a high-fat or chow diet. Interestingly, despite the absence of a body weight difference, Phox2b-Ntrk2+/− heterozygous mice exhibit pronounced hyperphagia. Conclusion: Taken together, our findings suggest that the hypothalamus is a key brain region involved in endogenous BDNF/TrkB signaling and central metabolic control and that endogenous hindbrain TrkB likely plays a role in modulating food intake and survival of mice. Our findings also show that female mice lacking TrkB in the hypothalamus have a more robust metabolic phenotype.